Determinants of livestock farmers’ adaptation strategies to climate change in Gandaki province, Nepal - KC, VIKASH KUMAR; DHUNGANA, ANANTA RAJ; KHAND, PURNA BAHADUR; UPADHAYAYA, RAJENDRA P; BARAL, MADHAB P (The Indian Journal of Animal Sciences, 2025)
Climate change is a global issue that has significantly impacted the agriculture and livestock sectors. Adaptation is a crucial approach to reducing the negative impact of climate change. This study identifies the key factors influencing livestock farmers’ adaptation to climate change in Gandaki Province, Nepal. A multi-stage random sampling technique was used to collect data from 1158 households in five districts (Mustang, Kaski, Tanahu, Nawalpur, and Gorkha) of Gandaki province, western Nepal. A pretested structured questionnaire for households and a checklist for FGDs were used to collect the data. This study utilized descriptive and inferential statistics. A binary logistic regression model was used to identify the determinants of livestock farmers’ adaptation strategies to climate change. Knowledge of climate change and its impact on livestock was common among farmers. Socioeconomic, demographic, climatic, agro-ecological settings and accessibility-related factors are responsible for adaptation strategies among livestock farmers. This study concludes that place of residence, availability of land for livestock, household size, agro-ecological setting, and access to credit are the determining factors in adaptation strategies to climate change impact in Gandaki Province, Nepal. The finding of this study may be beneficial in identifying the relevant adaptation strategies at the local level.